Procedure For Ship Arrival And Departure Document Management At PT. Seroja Jaya Agency Branch Kuala Tanjung - Ahmad Husni Irwansyah; Dirhamsyah Dirhamsyah; Dina Rispianti (Jurnal Publikasi Ilmu Manajemen, 2024)
This study was conducted to determine the process of implementing the procedures for managing ship arrival and departure documents to facilitate loading and unloading procedures. PT. Seroja Jaya Agency, Kuala Tanjung branch, handles types of ships, such as Container vessels, Motor Tankers, Bulk Carriers, Tug Boats and Barges. The important role of operational agents is very influential in the smooth running of ship arrival and departure activities when docking, loading/unloading, and sailing. Preparation of notifications and management of arrival permits are the main tasks of the agency before the ship arrives and departs, known as clearance in and clearance out. Qualitative research type, data collection techniques with interviews, observations and documentation.